A prospective investigation of the effects of soccer heading on cognitive and sensorimotor performances in semi-professional female players - Kern, Jan; Gulde, Philipp; Hermsdörfer, Joachim (Frontiers in Human Neuroscience, 2024)
Introduction Repetitive head impacts (RHI) from routine soccer (football) heading have been suggested to contribute to the long-term development of neurodegenerative disorders. However, scientific evidence concerning the actual risk of these RHI on brain health remains inconclusive. Moreover, female athletes—despite a presumably increased vulnerability toward the effects of RHI—are largely underrepresented in previous approaches. Therefore, our aim was to prospectively investigate the effects of heading on cognitive and sensorimotor performances, health perception, and concussion symptoms in semi-professional female soccer players. Methods An extensive test battery was used to assess cognitive and sensorimotor performances as well as health status (SF-36) and concussion symptoms (SCAT3) of a total of 27 female soccer players (22.2 ± 4.2 years) and 15 control subjects (23.2 ± 3.0 years) before and after one-and-a-half years. Throughout this period, soccer players’ heading exposure was determined using video analysis. Results Subgroup comparisons (control [n = 12], low exposure [n = 7], high exposure [n = 8]) showed no time-dependent differences in SF-36 or SCAT3 scores. Similarly, across most behavioral tests, soccer players’ performances evolved equally or more favorably as compared to the control subjects. However, there were significant effects pointing toward slightly negative consequences of heading on aspects of fine motor control (p = 0.001), which were confirmed by correlation and multiple regression analyses. The latter, further, yielded indications for a relationship between heading exposure and negative alterations in postural control (p = 0.002). Discussion Our findings do not provide evidence for negative effects of soccer heading on female players’ health perception, concussion symptoms, and cognitive performances over the course of one-and-a-half years. However, we found subtle negative alterations in fine motor and postural control that could be attributed to heading exposure. Other factors, like the number of previous head injuries, were not linked to the observed changes. Given the reduction of our initial sample size due to player fluctuation, the results need to be interpreted with caution and validated in larger-scale studies. These should not only focus on cognitive outcomes but also consider sensorimotor changes as a result of RHI from soccer heading.